Strengthening the resilience of small-scale fisheries: A modeling approach to explore the use of in-shore pelagic resources in Melanesia. (October 2017) - Hardy, P.-Y.; Béné, C.; Doyen, L.; Mills, D.
Abstract: Small-scale fisheries play a critical role in both poverty alleviation and food security. A large proportion of the world fish stocks are, however, getting fully or over-exploited. In this article we address these issues in the context of the small-scale fisheries of the Solomon Islands. The paper explores the extent to which in-shore Fish Aggregating Devices (FADs) can help increasing the resilience of the small scale fishery system and reconciling social, economic and ecological priorities. Based on the concept of 'time of crisis' developed recently in the viability literature, we propose to calculate a resilience index through a dynamic stochastic model calibrated by ethnological observations. The resilience index calculation reveals two major findings: (i) the resilience of the small scale fishery system is currently nonexistent and (ii) the introduction of FADs can improve it. The effects of the FADs' implementation are then discussed in the light of a socio-economic perspective. Such results bring new insights into the question of the future of the small scale fishery sector, especially in relation to the local economy evolution from a barter dominance to a cash oriented economy. At the same time, the current subsistence fisheries seems more resilient in general due to a distributive effects which ease the 'race for fish behaviors'. Finally, our analysis reveals that while the FADs implementation stands as a short and mid-term answer, demographic drivers are important and other alternatives will need to be considered if the overall viability of the system is to be maintained in the longer-term. Highlights: The small scale fishery sector's resilience has to be considered in terms of poverty alleviation, food security and biodiversity conservation. Dealing with data-poor situation, based on the viability framework and the concept of 'time of crisis', a resilience index can be measured. In our case, the fishery's resilience lasts for the 30 next years only if a pelagic resource is available through FADs and if a small sale increase occurs. In our case, the subsistence driven economy shows resilient properties based on a minimum allocation of the catch for direct consumption.